2020
DOI: 10.3390/nano10051005
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Layer Phase Composition-Dependent Photoactivity of One-Dimensional TiO2–Bi2O3 Composites

Abstract: TiO2–Bi2O3 composite rods were synthesized by combining hydrothermal growth of rutile TiO2 rod templates and sputtering deposition of Bi2O3 thin films. The TiO2–Bi2O3 composite rods with β-Bi2O3 phase and α/β-Bi2O3 dual-phase decoration layers were designed, respectively, via in situ radio-frequency magnetron sputtering growth and post-annealing procedures in ambient air. The crystal structure, surface morphology, and photo-absorption performances of the pristine TiO2 rods decorated with various Bi2O3 phases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Furthermore, as demonstrated in the aforementioned results, the existence of the ZnO/Bi 2 O 3 heterojunction also improved the charge separation efficiency of the composite. Similar improved photocatalytic abilities owing to the existence of a heterojunction with suitable band alignment between the constituent oxides have been demonstrated in other oxide heterostructures 1,32 …”
Section: Resultssupporting
confidence: 60%
“…Furthermore, as demonstrated in the aforementioned results, the existence of the ZnO/Bi 2 O 3 heterojunction also improved the charge separation efficiency of the composite. Similar improved photocatalytic abilities owing to the existence of a heterojunction with suitable band alignment between the constituent oxides have been demonstrated in other oxide heterostructures 1,32 …”
Section: Resultssupporting
confidence: 60%
“…The signicant increase in photocurrent density of the Bi 2 O 3 photoelectrode under irradiation indicates the improved separation ability of photogenerated electron (e À )-hole (h + ) pairs in semiconductor oxides. 2,3 The transient photocurrent density vs. time curves results herein demonstrated that the 10S-Bi 2 O 3 photoelectrode exhibited the superior photoinduced electron-hole separation efficiency among various Bi 2 O 3 photoelectrodes. Notably, the photocurrent density of the Bi 2 O 3 photoelectrodes with a dual a/b-Bi 2 O 3 phase is signicantly higher than that of the Bi 2 O 3 photoelectrodes with a pure b-Bi 2 O 3 phase under the similar synthesis solution pH value but with and without seed layer assisted growth, indicating that the a/b homojunction is effective to separate the photoinduced electron-hole pairs.…”
Section: Resultsmentioning
confidence: 68%
“…Bi 2 O 3 is an environmental friendly material, and it has received much attention due to its unique electrical and optical properties, which leads to its extensive usage in various scientic devices. [1][2][3] Furthermore, it is a promising visible-light-driven photocatalyst with a narrow band gap (2.0-2.9 eV), and the valence band of bismuth oxide is made of a hybrid Bi 6s and O 2p orbit that decreases the symmetry of the band structure and leads to the corresponding dipoles which could enhance its photoactivity. 4 Bi 2 O 3 has different polymorphs; 5 the monoclinic a and tetragonal b phases have been reported to exhibit superior photoactivity among various polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Among these strategies, constructing a TiO 2 -based heterojunction with a visible-light sensitizer is proved to be a promising approach to enhance the photoactive performance of TiO 2 . 1,8,9 Among various visible-light sensitizers, cuprous oxide (Cu 2 O) is an important narrow band gap and p-type semiconductor. 1,10 Diverse synthesis approaches of Cu 2 O also make it widely used as a photosensitive material.…”
Section: Introductionmentioning
confidence: 99%